Foreign player quota, experience and efficiency of basketball players - Ozmen, M. U. (Journal of Quantitative Analysis in Sports, 2012)
This study analyzes how the efficiency of basketball players depends on experience, player`s nationality and team type. Using data for players in the Turkish Basketball League (TBL) from 1997 to 2010, we first show that efficiency of players initially increase with experience, but after a certain level decrease with it. Second, foreign players are on average more talented than native players. Third, the experience-efficiency link is not valid for foreign players indicating that more experience does not affect efficiency. Fourth, efficiency of foreign players in top-teams is no different than that of foreign players in regular (non-top) teams; whereas, native players in top-teams are more efficient than native players in other teams. Finally, in the presence of foreign player quota, top-teams hire the maximum number of foreign players allowed, while financially constrained regular teams can afford less foreign players. Consequently, under foreign player quota the quality of native players and the extent to which a team can pay for additional foreign players determine the team success.